Analysis of household food procurement practices from a sustainability perspective in grand Lomé, Togo - Nabagou, Moyéme; Kpotchou, Koffi (Edelweiss Applied Science and Technology, 2024)
Over the past ten years, African cities have been trying to move towards sustainable food supply by setting up short food distribution circuits (CCs). This article analyzes household behavior towards CCs in Grand Lomé, Togo, using a survey of 963 randomly sampled households, 13 focus groups, 6 individual interviews, as well as observation. Excel spreadsheets and R-Studio software were used to process and analyze quantitative data, while content analysis was applied to the verbal statements collected. At the end of the surveys, multiple-choice questions enabled us to detect, firstly, a low level of use of CCs, with 8.79%, 7.73% and 4.66% of respondents respectively resorting to "online purchasing", "self-production of food" and "the farmer's home". On the other hand, 92.37% of households go to public markets and 81.99% use informal food shops. Next, a correlation was observed between the "type of shop" frequented and "profession" : salaried workers, shopkeepers and students go to quality shops, while artisans make do with lower-quality shops. Finally, the main reasons for visiting markets are "affordability" and "physical proximity", while "quality" and the "local character of the food" are less important. Actions are proposed to increase the role of CCs in this city.